Pelatihan Perancangan dan Penggunaan Multimedia Interaktif Articulate Storyline 3 Berbasis Pendekatan CTL untuk Memberdayaan Guru di Sekolah Dasar - Reinita Reinita; Atri Waldi; Rifda Eliyasni; Farida S; Ari Suriani; Ahmad Zikri (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The purpose of this article is to improve the knowledge, understanding and skills of elementary school teachers in Batang Gasan District, Padang Pariaman Regency based on Community Service activities that have been carried out. This program is carried out in the form of training and meetings. Presentation materials include the nature of learning media, interactive multimedia Articulate Storyline 3, with Contextual Teaching and Learning (CTL) Approach in integrated thematic learning. The method used in the interactive multimedia training of Articulate Storyline 3 is the lecture method, question and answer, assignment and discussion. This program is focused on training in the creation and use of learning media in accordance with the Industrial Revolution Era 4.0, namely media that are in accordance with the times and technological involvement, with the introduction of an understanding of the media can increase teacher motivation for technology-based media users to be able to support creativity and new innovations. for teachers in designing media. This training can improve the skills and professionalism of teachers to design media used in learning practices so that learning messages are conveyed and attract the attention of students.